Implement Electrostatic Precipitator Maintenance to Prevent Damage: Mengimplementasikan Perawatan Electrostatic Precipitator Untuk Mencegah Terjadinya Kerusakan - Maulidani, Muhammad Faza; Wisaksono, Arief (Procedia of Engineering and Life Science, 2025)
Electrostatic machines have an important role in various industries because of their ability to support production processes efficiently. However, the reliability and performance of these machines can be compromised by potential damage due to lack of proper maintenance. This article aims to discuss effective strategies for implementing electrostatic machine maintenance to prevent damage and extend its operational life. Approaches discussed include routine inspections, condition monitoring, regular cleaning, and the use of predictive technology to detect potential problems. Through implementing this strategy, companies can minimize the risk of operational disruptions, increase production efficiency, and reduce unexpected repair costs. Case studies and practical recommendations are also presented to provide deeper insights for practitioners and industry stakeholders.